2023
DOI: 10.1039/d2mh00970f
|View full text |Cite
|
Sign up to set email alerts
|

Green-solvent-processed formamidinium-based perovskite solar cells with uniform grain growth and strengthened interfacial contact via a nanostructured tin oxide layer

Abstract: The green-solvent-processed perovskite solar cells (PSCs) have reached an efficiency of 20%, showing a great promise in safe industrial production. However, the nucleation process in green-solvent-based deposition is rarely optimized,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…(A) Environmental health & safety assessment of different solvents in perovskite solar cell (PVSC) fabrication 110 . (B) Schematic of the fabrication procedures of the green‐solvent process of the perovskite based on SnO 2 ‐nanorods (NRs) and SnO 2 ‐nanoparticles (NPs) substrates, respectively 111 . Reproduced from permission, copyright 2023, the Royal Society of Chemistry.…”
Section: Eco‐friendly Device Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…(A) Environmental health & safety assessment of different solvents in perovskite solar cell (PVSC) fabrication 110 . (B) Schematic of the fabrication procedures of the green‐solvent process of the perovskite based on SnO 2 ‐nanorods (NRs) and SnO 2 ‐nanoparticles (NPs) substrates, respectively 111 . Reproduced from permission, copyright 2023, the Royal Society of Chemistry.…”
Section: Eco‐friendly Device Processingmentioning
confidence: 99%
“…The form of TEP-PbI 2 intermediate phase via the coordination effects between P O and Pb 2+ enables dense and uniform perovskite films (Figure 3B). 111,114 Recently, molten salt methylammonium acetate (MAAc) has been developed as an ideal green solvent to realize perovskites with high quality and superior stability due to its strong interaction with perovskites via the Ac À and Pb 2+ . 115 For partial solvent replacement, Tang et al substitute DMF with non-toxic N,N-diethylformamide (DEF) to form DEF/DMSO mixed solvent.…”
Section: Eco-friendly Perovskite Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Wu et al have successfully produced high efficiency formamidinium based perovskite cells reaching PCEs of 22.4% using the green solvent triethyl phosphate. 299,300 Many factors influence PCE and not all labs are able to achieve record efficiencies even with solvents such as DMF. Doolin et al demonstrated that when a fair comparison to evaluate their green solvent systems side by side against DMF was made, comparable cell efficiencies were achieved.…”
Section: Materials Considerationsmentioning
confidence: 99%
“…17 Other studies have also demonstrated the efficacy of the Ostwald ripening process in enhancing the optoelectronic properties of perovskite films. 18,19 However, it is difficult to accurately control the secondary growth of Ostwald process-induced films. In other words, uncontrolled Ostwald processes may be accompanied by the production of residual PbI 2 , 20 which could hinder carrier transmission and further degrade device performance.…”
Section: Introductionmentioning
confidence: 99%